Visual Narrative and Temporal Relevance: Segueing Instant Replay into Live Broadcast TV. Issue 1 (7th January 2019) - Perry, Mark; Broth, Mathias; Engström, Arvid; Juhlin, Oskar
Abstract : Professional production of live TV combines real‐time and recorded video into a single broadcast stream. In "live" TV, non‐live "instant replay" footage can help viewers to make sense of what has just happened. This article shows how multi‐person TV production teams assemble timely and relevant instant replays that can be seamlessly combined with real‐time footage during live broadcasts. Detailed interaction analysis demonstrates how this work is dependent on coordinated practices, and how team members achieve this by orienting to narrative concerns across multiple temporalities to produce topically useful instant replays, displaying clip relevance, and help segueing transitions between the ongoing action and replay. We conclude by examining the interrelationships between the sequential flow of visual content, the role of talk in mediating time‐shifted visual alignments, and how members make their work visible and accountable to one another and to their intended audience.